CONTROL ADHERENCE OF HYPERTENSIVE PATIENTS AT POSYANDU ILP - Ika Afriza Nikmah; Awan Hariyanto; Mimik Christiani (Indonesian Health Literacy Journal, 2026)
Hypertension remains one of the leading causes of cardiovascular morbidity and mortality worldwide. Regular follow-up visits are essential to maintain control of blood pressure and prevent complications. However, adherence to scheduled health controls among hypertensive patients remains a major challenge, particularly at the primary healthcare level. This study aimed to describe control adherence among hypertensive patients attending Posyandu Integrasi Layanan Primer (ILP) Mars in the working area of Trenggalek Primary Health Center.A descriptive quantitative study was conducted involving 24 hypertensive patients selected using accidental sampling from a population of 50 patients. Data was collected using structured questionnaires between April and May 2026 and analyzed using descriptive (univariate) statistics. Most respondents were female (91.7%), aged 58–67 years (58.3%), had elementary school education (50%), and had attended Posyandu ILP for more than one year (54.2%). Overall, 83.3% of respondents demonstrated adherence to scheduled hypertension control visits. Most hypertensive patients attending Posyandu ILP Mars demonstrated good adherence to routine follow-up visits. Continuous health education and strengthening community-based primary healthcare programs are necessary to sustain patient adherence and reduce hypertension-related complications.